A role for LSH in facilitating DNA methylation by DNMT1 through enhancing UHRF1 chromatin association. Issue 21 (10th November 2020) - Han, Mengmeng; Li, Jialun; Cao, Yaqiang; Huang, Yuanyong; Li, Wen; Zhu, Haijun; Zhao, Qian; Han, Jing-Dong Jackie; Wu, Qihan; Li, Jiwen; Feng, Jing; Wong, Jiemin
Abstract: LSH, a SNF2 family DNA helicase, is a key regulator of DNA methylation in mammals. How LSH facilitates DNA methylation is not well defined. While previous studies with mouse embryonic stem cells (mESc) and fibroblasts (MEFs) derived from Lsh knockout mice have revealed a role of Lsh in de novo DNA methylation by Dnmt3a/3b, here we report that LSH contributes to DNA methylation in various cell lines primarily by promoting DNA methylation by DNMT1. We show that loss of LSH has a much bigger effect in DNA methylation than loss of DNMT3A and DNMT3B. Mechanistically, we demonstrate that LSH interacts with UHRF1 but not DNMT1 and facilitates UHRF1 chromatin association and UHRF1-catalyzed histone H3 ubiquitination in an ATPase activity-dependent manner, which in turn promotes DNMT1 recruitment to replication fork and DNA methylation. Notably, UHRF1 also enhances LSH association with the replication fork. Thus, our study identifies LSH as an essential factor for DNA methylation by DNMT1 and provides novel insight into how a feed-forward loop between LSH and UHRF1 facilitates DNMT1-mediated maintenance of DNA methylation in chromatin.